Intergenerational and Sibling Spillovers in High School Majors - Gordon B. Dahl; Dan-Olof Rooth; Anders Stenberg (Institute of Labor Economics (IZA), 2023)
This paper estimates family spillovers in high school major choice in Sweden, where admission to oversubscribed majors is determined based on GPA. Using a regression discontinuity design, we find large sibling and intergenerational spillovers that depend on the gender mix of a dyad. Same-gender siblings copy one another, while younger brothers recoil from older sister's choices. Fathers and mothers influence sons, but not their daughters, except when a mother majors in the male-dominated program of Engineering. Back of the envelope calculations reveal these within family spillovers have sizable implications for the gender composition of majors.
Keywords: I21; J24; 330; intergenerational spillovers; sibling spillovers; high school majors; gender composition of majors